Pengaruh segmentasi pasar terhadap kepuasan pelanggan (nasabah) pada Bank BPR Jatim Cabang Ponorogo - Elis Tri Wahyuni (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2017)
This study aims to determine the effect of market segmentation of customer satisfaction (Customer) in bank BPR Jatim Branch of Ponorogo. Market Segmentation effect on customer satisfaction as evidenced from t value on the market cementation variable (X) is from a significant level of 0.000 t less than 0.05 then the research hypothesis H0 and menerimaHa resisting. And it can be seen the value rhitung is 0.748 while rtabel 0,138. This constant value of 10.264 means if the variable value market segmentation fixed or constant, the amount of customer satisfaction (customers) amounted to 10.264. This means that in the absence of market segmentation variables pegaruh then customer satisfaction still has a value of 10.264.